Pulmonary artery pulsatility indexes in differentiating chronic pulmonary thromboembolism from pulmonary arterial hypertension - Palecek, Tomas; Jansa, Pavel; Ambroz, David; Hlubocka, Zuzana; Horak, Jan; Skvarilova, Marcela; Aschermann, Michael; Linhart, Ales (Current medical research and opinion, 2007)
ABSTRACT Background: The differentiation between chronic pulmonary thromboembolic hypertension (CTEPH) and pulmonary arterial hypertension (PAH) remains a clinical challenge. Recently, it has been suggested that pulmonary artery pulsatility indexes, determined either invasively or noninvasively, could enable the discrimination between CTEPH and PAH. Aim of the study: To evaluate the usefulness of both echocardiographically- and invasively-derived pulmonary artery pulsatility indexes in the etiologic differentiation of patients with CTEPH and PAH. Methods: We retrospectively analyzed the results of echocardiographic and invasive hemodynamic examinations in 97 patients with either CTEPH (n = 48) or PAH (n = 49). Using echocardiography, pulmonary artery systolic (PASP), diastolic (PADP) and mean (PAMP) pressures were estimated from velocities of tricuspid regurgitation and pulmonary regurgitation, respectively. Invasive data were obtained in 39 patients with CTEPH and 44 patients with PAH using a fluid-filled system that included a balloon-tipped flow catheter. Pulse pressure (PP) was calculated as a difference between PASP and PADP. To obtain pulmonary artery pulsatility indexes, we normalized PP by PASP (PP/PASP), by PAMP (PP/PAMP) and by PADP (PP/PADP). Results: Pulsatility indexes assessed by echocardiography did not differ between CTEPH and PAH patients. Invasively-derived pulsatility indexes were significantly higher in subjects with CTEPH (0.59 ± 0.09 vs. 0.52 ± 0.10 for PP/PASP; 0.95 ± 0.23 vs. 0.77 ± 0.19 for PP/PAMP; 1.52 ± 0.53 vs. 1.14 ± 0.37 for PP/PADP; all p < 0.01). The areas under the receiver-operating characteristic curves analysis were 0.68 (95% CI 0.55–0.79), 0.7 (95% CI 0.58–0.81), and 0.68 (95% CI 0.55–0.79) for invasively-derived PP/PASP, PP/PAMP and PP/PADP, respectively. Conclusions: Invasively-derived PP and pulmonary artery pulsatility indexes are higher in CTEPH compared to PAH. However, due to the important overlap, no optimal threshold values of these parameters can be given to allow satisfactory discrimination between the two diseases. Therefore, these indexes do not permit clear etiologic differentiation of CTEPH and PAH in clinical practice.